2008
DOI: 10.1021/jm7013452
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences of Natural and C3-Modified Epothilones in Aqueous Solution

Abstract: The conformational properties of the microtubule-stabilizing agent epothilone A ( 1a) and its 3-deoxy and 3-deoxy-2,3-didehydro derivatives 2 and 3 have been investigated in aqueous solution by a combination of NMR spectroscopic methods, Monte Carlo conformational searches, and NAMFIS calculations. The tubulin-bound conformation of epothilone A ( 1a), as previously proposed on the basis of solution NMR data, was found to represent a significant fraction of the ensemble of conformations present for the free lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 44 publications
17
80
0
Order By: Relevance
“…[22] These findings have been reconfirmed in this study, even if the EC 50 value for 2 is somewhat higher than previously reported (Table 1). [22] In contrast, more distinct activity differences are present between 2, 3, and Epo A (1 a) at the level of cancer cell growth inhibition, with analogue 2 being clearly less active than 3 and, in particular, Epo A (1 a) ( Table 2).…”
Section: C3-modified Epothilonessupporting
confidence: 88%
See 3 more Smart Citations
“…[22] These findings have been reconfirmed in this study, even if the EC 50 value for 2 is somewhat higher than previously reported (Table 1). [22] In contrast, more distinct activity differences are present between 2, 3, and Epo A (1 a) at the level of cancer cell growth inhibition, with analogue 2 being clearly less active than 3 and, in particular, Epo A (1 a) ( Table 2).…”
Section: C3-modified Epothilonessupporting
confidence: 88%
“…[22] Overall, the conformation of 1 a, 2, and 3 in water closely resembled the NMR-derived structure of tubulin-bound Epo A (1 a); [21] in particular, a strong preference was observed for an antiperiplanar C1-C2-C3-C4 torsion, even in the case of 2. These findings suggested that 2 and 3 would also show similar tubulin-bound conformations as Epo A (1 a), but this hypothesis needed to be confirmed experimentally.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…16 A recent study showed that the 3-hydroxyl group may not be directly involved in the fundamental network of interactions between epothilones and b-tubulin. 17 This suggested that the less potent of 1 and 2, than epothilone B, may be attributed to the change of conformation of the Five new epothilone metabolites from S. cellulosum J Wang et al 16-membered macrolide framework influenced by the 3-a-D-arabinofuranoside moiety. Further work should be carried out to clarify the conformation of 1 and 2 and the structure-activity-relationship of C-3-substituted epothilones.…”
Section: Biological Activitymentioning
confidence: 99%